Evolutionary characteristics of mass movement in two adjacent debris flow gullies at the Great Bend of the Yarlung Zangbo River - Yunhong Lv; Cong Dai; Shuai Zhang; Yanbo Chen; Ying Lai; Limin Zhang; Bate Bate (Geomatics, Natural Hazards & Risk)
Debris flows have occurred in two adjacent gullies, namely Sedongpu Gully (SDP) and Zelongnong Gully (ZLN), since the 1950s. The most recent event occurred in ZLN in 2020, causing damage to human communities and infrastructure. Despite their close geographical proximity to the Great Bend of the Yarlung Zangbo River, SDP has experienced more frequent and severe events compared to ZLN. This paper aims to compare the evolutionary characteristics of mass movement between these two gullies. A comprehensive review of 12 debris flow events in both gullies from 1950 to 2020 was conducted. A novel method was proposed and verified for quantifying the debris flow mass movement by integrating InSAR, multi-DSMs, optical images, and field investigations. Comparative analysis revealed distinct evolutionary stages between the gullies, with SDP exhibiting mixed hillslope and channelized debris flows, whereas ZLN primarily experienced channelized debris flows. SDP witnessed a decrease in rainfall and temperature triggering debris flows, contrasting with ZLN where both factors increased. These explained the smaller frequency and magnitude of debris flows in ZLN. Overall, this study emphasizes the need for tailored risk prevention and control measures that reflect the specific dynamics of each gully.